A rapid test for assessing disease activity in ulcerative colitis - Dranga, Mihaela; Mihai, Catalina; Drug, Vasile; Dumitrescu, Gabriela; Prelipcean, Cristina Cijevschi (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Direct assessment by endoscopic examination has become a “gold standard” in monitoring patients with ulcerative colitis. However, it is an invasive method, with risks and discomfort for the patients. The aim is therefore to identify a less invasive method of assessing ulcerative colitis activity compared to colonoscopy. Materials and Methods: A prospective study was conducted among 103 patients with ulcerative colitis. Calprotectin was measured by a semi-quantitative rapid test. For each patient, a complete blood count was performed; liver and kidney functions, glycaemia, serum proteins, and inflammatory markers were also evaluated. Results: The Mayo score showed direct correlations with fecal calprotectin, C-reactive protein, and the erythrocyte sedimentation rate (p<0.05) and indirect correlations with hemoglobin (p=0.139). The sensitivity and specificity of calprotectin were 98.0% and 76.7%, respectively. Subsequently, combined analysis of the markers’ sensitivity/specificity was conducted. Conclusion: The semi-quantitative rapid test proved to be a good predictor for differentiating the endoscopic active disease from the inactive one. The individual use of fecal calprotectin presents the highest sensitivity in determining the endoscopic activity. Nevertheless, in monitoring patients, combined determination of the three inflammatory markers studied [C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), calprotectin] is more useful in reducing unnecessary colonoscopies.